Nafion® and polyaniline composite modification with Li and Mg ions. (March 2019) - Lozkins, Stanislavs; Hodakovska, Julija; Kleperis, Janis; Merijs-Meri, Remo
Abstract: Modification of Nafion®-based samples with polyaniline (PANI) and positive charged ions could potentially allow achieving good proton conductivity at higher working temperatures what is observed in typical polymer electrolyte membrane fuel cells. In this work Nafion® polymer was modified with 1% polyaniline emeraldine salt and Li and Mg ions containing solutions. The influence of activation process and the type of ions on composites' proton conductivity was investigated. To define the best composition the physiochemical properties of synthesized materials were determined by the means of thermogravimetric analysis, impedance spectroscopy, determination of water absorption and its kinetics, and FTIR. From the original samples the best results of σ=155 mS/cm were shown by Nafion®/PANI membrane what was modified by Li+ reduction solution. This membrane also had better thermal characteristic compared to other researched samples: membrane degradation starts on higher temperature interval.